Autoimmune encephalitis. Issue 2 (February 2016) - Newman, M. P.; Blum, S.; Wong, R. C. W.; Scott, J. G.; Prain, K.; Wilson, R. J.; Gillis, D.
Abstract : Over the past decade, the clinical spectrum of autoimmune encephalitis has expanded with the emergence of several new clinicopathological entities. In particular, autoimmune encephalitis has recently been described in association with antibodies to surface receptors and ion channels on neurological tissues. Greater clinician awareness has resulted in autoimmune encephalitis being increasingly recognised in patients with unexplained neurological and psychiatric symptoms and signs. The clinical spectrum of presentations, as well as our understanding of disease mechanisms and treatment regimens, is rapidly developing. An understanding of these conditions is important to all subspecialties of Internal Medicine, including neurology and clinical immunology, psychiatry, intensive care and rehabilitation medicine. This review provides a contemporary overview of the aetiology, investigations and treatment of the most recently described autoimmune encephalitides.